2015
DOI: 10.1002/jcop.21670
|View full text |Cite
|
Sign up to set email alerts
|

What Can We Learn? Examining Intimate Partner Violence Service Provision in the Deaf Community

Abstract: Recent community-based research indicates that the prevalence of intimate partner violence (IPV) in the Deaf community exceeds known rates among hearing individuals, yet little is known about services available to Deaf IPV victims. Given the inaccessibility of IPV services, providers (doctors, psychologists, and lawyers) who know American Sign Language become IPV providers while addressing myriad comorbid issues that affect Deaf clients. This article presents data drawn from transcripts of semistructured inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Moreover, Deaf community leaders tend to focus their attention on discrimination, interpreter services, oppression (e.g., protecting sign language and schools for the deaf from detractors), and the general lack of accessible services for the Deaf community, with less prioritization on specialized services, such as IPV services (Merkin & Smith, 1995). While more recent work notes that there have been increases in the number of Deaf IPV service organizations, this work also found that overall “most IPV providers serving hearing people are IPV specialists, whereas the providers serving Deaf people are usually generalists, required to address an array of complicated needs for their clients due to their unique accessibility of ASL users” (Cerulli et al, 2015, p. 151). One study of women with disabilities and women who are deaf found participants often relied on informal, as opposed to formal, sources of support; findings consistent with female IPV victims without disabilities (Powers et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, Deaf community leaders tend to focus their attention on discrimination, interpreter services, oppression (e.g., protecting sign language and schools for the deaf from detractors), and the general lack of accessible services for the Deaf community, with less prioritization on specialized services, such as IPV services (Merkin & Smith, 1995). While more recent work notes that there have been increases in the number of Deaf IPV service organizations, this work also found that overall “most IPV providers serving hearing people are IPV specialists, whereas the providers serving Deaf people are usually generalists, required to address an array of complicated needs for their clients due to their unique accessibility of ASL users” (Cerulli et al, 2015, p. 151). One study of women with disabilities and women who are deaf found participants often relied on informal, as opposed to formal, sources of support; findings consistent with female IPV victims without disabilities (Powers et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 92%
“…These data come from a three-phase research project that examined the etiology of IPV affecting the Deaf community (see Cerulli et al, 2015). This article focuses on the second phase of the project, the purpose of which was to gather data from deaf IPV victims in an effort to investigate and describe risk and protective factors for IPV behaviors in relationships involving one or more deaf individuals who use ASL, with attention to specific factors associated with greater injury and mortality risk.…”
Section: Methodsmentioning
confidence: 99%
“…Recent findings from a study of ASL-fluent service providers working with Deaf survivors of IPV observed that while service providers working with hearing survivors tend to be IPV specialists, those serving Deaf survivors tend to be “generalists, required to address an array of complicated needs for their clients due to their unique accessibility to ASL users” (Cerulli et al, 2015, p. 151). Because these providers tend to be housed in non-IPV-specific service agencies, they may find themselves working with both perpetrators and survivors, which presents troubling confidentiality concerns.…”
Section: Discussionmentioning
confidence: 99%
“…It is important for researchers and practitioners to consider the intersection of various identities, including race, ethnicity, gender, age, disability, social class, and immigration, as these identities shape the opportunities available to women as they consider their options when addressing IPV (Child, Oschwald, Curry, Hughes, & Powers, 2011). The ability to find and access appropriate services may be further challenged when clients present with a range of unique issues, such as when a Deaf survivor has immigration-related concerns and faces barriers related to both communication and citizenship (Cerulli et al, 2015). A survivor's education history has an impact on resource knowledge and vocational options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation